A comparative study between the use of the combination of trichloroacetic acid peeling with hydroquinone and hydroquinone alone in patients with melasma - Adhikari, Sabina; Sushil Karki,; Anand Nepal,; Kathit Raj Ghimire, (Asian Journal of Medical Sciences, 2023)
Background: Melasma is a common acquired pigmentary disorder that is aesthetically displeasing. Kligman’s and Modified Kligman’s formula using topical steroids, hydroquinone and retinoids, and various other depigmenting agents is being widely used all over for melasma with varying results. Chemical peeling is newly added to the therapeutic armamentarium and is showing encouraging results worldwide in patients with melasma. However, comparative studies are lacking in abundance in our part of the world. Aims and Objectives: To determine if serial trichloroacetic acid peels provide additional benefits when combined with time-tested topical therapy with hydroquinone 4% in patients with melasma. Materials and Methods: Fifty melasma patients were divided into two groups of 25 each. One group received serial trichloroacetic acid peel combined with topical hydroquinone 4%. The other group only received topical hydroquinone 4% cream. The results were evaluated by a clinical investigator both subjectively and with photographs taken at baseline, 12 weeks, and 21 weeks. For clinical evaluation, the melasma area and severity index (MASI) was used. Results: A significant decrease in MASI score from baseline to 21 weeks was observed in both groups (P<0.001). The group receiving the trichloroacetic acid peel 20% showed a trend toward more rapid and greater improvement, with statistically significant results (P<0.001). Only a few side effects were observed in the peel group. Conclusion: This study demonstrates that serial trichloroacetic acid peels provide an additional effect to a topical regimen of 4% hydroquinone cream for treating melasma in Fitzpatrick skin types III and above if used judiciously and under supervision. It demonstrates that superficial chemical peels can be used as an adjunct with better efficacy to treat patients with melasma.